Study on the feeding behaviour of house shrew (Suncus murinus L.) in Bogor to feed and rodenticide - Swastiko Priyambodo; Rianita Septiana (Universitas Trunojoyo Madura, 2022)
Shrew is an animal belong to small mammals that the existence must be noticed because it has defecation behavior and their droplets often pollutes the house. Shrew can be vectors in the spread of infectious diseases to human. Shrew management has not been conducted well. Information about the most preferred bait and the effective rodenticide as a reference in controlling is not widely known. Chemical control using rodenticides is effective enough and does not take a long time. The objective of this research was to obtain shrew preference to the types of feed that commonly consumed by human and rodenticide to control it. It can be used as bait in trapping and poisoned bait which are effective in shrew management. Baits that used were cooked rice, rice, white bread, Tenebrio larvae, cricket, chicken nugget, fish meatball, and salted fish. Choice tests were used by serving eight feeds in one cage for seven consecutive days in the first test. Then, choose four prefered feeds and tested for seven consecutive days in the second test. Acute poison (zinc phosphide) and chronic poison (coumatetralyl) mixed with the most preferred feed, then served with control feed as comparison for the third test. Result of this research showed that cricket was the most preferred feed therefore it can be used as trap bait or poisoned bait. Moreover, the other most preferred feed is Tenebrio larvae, fish meatball, and cooked rice that can be used as substitution feed if crickets are difficult to find. Zinc phosphide rodenticide is more effective than coumatetralyl to kill shrew with relatively fast on the time of death.